An Efficient Sky Detection Algorithm from Fisheye Image Based on Region Classification and Segment Analysis. (2017) - Bourr, Houssam; Merabet, Youssef El; Messoussi, Rochdi; Benmiloud, Ibtissam; Ruichek, Yassine
No abstract available